Correction: Comment on "Negative effective Li transference numbers in Li salt/ionic liquid mixtures: does Li drift in the "Wrong" direction?" by M. Gouverneur, F. Schmidt and M. Schönhoff, Phys. Chem. Chem. Phys., 2018, 20, 7470. Issue 2 (12th December 2018) - Harris, Kenneth R.
Abstract : Correction for 'Comment on "Negative effective Li transference numbers in Li salt/ionic liquid mixtures: does Li drift in the "Wrong" direction?" by M. Gouverneur, F. Schmidt and M. Schönhoff, Phys. Chem. Chem. Phys., 2018, 20, 7470' by Kenneth R. Harris, Phys. Chem. Chem. Phys., 2018, 20, 30041–30045.